Predicting Student Graduation Grades Using the C4.5 Algorithm: An Implementation Study - Wiranti, Bela amlia Amalia; Supriyanto, Supriyanto; Nurmayanti, Nurmayanti (LPPM Universitas Islam 45 Bekasi, 2024)
SMP KEMALA BHAYANGKARI as one of the private schools, students follow the learning process and are carried out mid-semester exams, semester final exams in completing junior high school level education. test scores as one of the requirements for grade promotion or for graduation mark the end of junior high school level, and the value of knowledge is one of the keys to a person's ability to complete education. predicting student graduation with the C4.5 algorithm method In the application of the C4.5 algorithm using Rapidminer tools, after manual calculation, the results will be tested using Rapidminer tools. the results of manual calculation of the C4.5 algorithm and the results of calculations using rapidminer tools will produce an Accuracy Level resulting from this calculation of 92.22% for graduation grades at SMP Kemala Bhayangkari Kotabumi.